Financial literacy: A systematic review and bibliometric analysis - Goyal, Kirti; Kumar, Satish (International journal of consumer studies, 2021)
Given the paucity of comprehensive summaries in the extant literature, this systematic review, coupled with bibliometric analysis, endeavours to take a meticulous approach intended at presenting quantitative and qualitative knowledge on the ever‐emerging subject of financial literacy. The study comprises a review of 502 articles ‐ published in peer‐reviewed journals from 2000 to 2019. Citation network, page‐rank analysis, co‐citation analysis, content analysis and publication trends have been employed to identify influential work, delineate the intellectual structure of the field and identify gaps. The most prominent journals, authors, countries, articles and themes have been identified using bibliometric analysis, followed by a comprehensive analysis of the content of 107 papers in the identified clusters. The three major themes enumerated are—levels of financial literacy amongst distinct cohorts, the influence that financial literacy exerts on financial planning and behaviour, and the impact of financial education. Additionally, content analysis of 175 papers has been conducted for the last four years’ articles that were not covered in the co‐citation analysis. Emerging themes identified include financial capability, financial inclusion, gender gap, tax & insurance literacy, and digital financial education. A conceptual framework has been modelled portraying the complete picture, following which potential areas of research have been suggested. This study will help policy‐makers, regulators and academic researchers know the nuts and bolts of financial literacy, and identify the relevant areas that need investigation.